Simulation-Guided Analysis towards Trench Depth Optimization for Enhanced Flexibility in Stretch-Free, Shape-Induced Interconnects for Flexible Electronics - Joch, Daniel; Lang, Thomas; Sanctis, Shawn; Jank, Michael P.M. (Materials, 2024)
In this paper, we present an optimization of the planar manufacturing scheme for stretch-free, shape-induced metal interconnects to simplify fabrication with the aim of maximizing the flexibility in a structure regarding stress and strain. The formation of trenches between silicon islands is actively used in the lithographic process to create arc shape structures by spin coating resists into the trenches. The resulting resist form is used as a template for the metal lines, which are structured on top. Because this arc shape is beneficial for the flexibility of these bridges. The trench depth as a key parameter for the stress distribution is investigated by applying numerical simulations. The simulated results show that the increase in penetration depth of the metal bridge into the trench increases the tensile load which is converted into a shear force Q(x), that usually leads to increased strains the structure can generate. For the fabrication, the filling of the trenches with resists is optimized by varying the spin speed. Compared to theoretical resistance, the current–voltage measurements of the metal bridges show a similar behavior and almost every structural variation is capable of functioning as a flexible electrical interconnect in a complete island-bridge array.
CRIS-Team Scopus Importer:2024-08-16
Keywords: fabrication strategy; island-bridge; mechanical design; numerical simulation; stretchable electronics; structural design